Effects of CO2/rock/formation brine parameters on CO2 injectivity for sequestration - Md Yusof, M.A. (Offshore Technology Conference, 2020)
CO2 injection into saline aquifer has gained attention as an effective technique to permanently secure the produced anthropogenic gas from high CO2 gas field in South East Asia region. However, problem such as injectivity impairment has been faced by operators and researcher has attributed the interactions between CO2-brine-rock to be the major cause. This research investigated the effect of CO2 displacement schemes, reservoir rock permeability, formation brine type and concentration on CO2 injectivity. CO2 coreflood experiment with detailed characterization of the rock and effluent produced are presented. Various core samples which represent low and high permeability of typical geological storage for sequestration were selected. The core samples were analyzed using X-Ray Fluorescence (XRF), X-Ray Powder Diffraction (XRD) and Field Emission Scanning Electron Microscopy equipped with Energy Dispersive Spectroscopy (FESEM-EDX). Then it was saturated with synthetic formation brine composed of 6,000 ppm, 30,000 ppm or 50,000 of either Sodium Chloride (NaCl), Potassium (KCl) or Calcium Chloride (CaCl2). Lastly, core samples were injected by either supercritical CO2 (scCO2), CO2-saturated brine and combination of CO2saturated brine and scCO2 and the pressure drop profile was recorded. Fines were then being separated from the collected effluent for further analysis. FESEM images of the pre- and post-injection core samples were compared to assess physical changes. Results indicated that CO2 injection scheme, flow rate, brine concentration and initial rock permeability are the principal factors that contribute to the porosity and permeability alteration of the core samples. Moreover, FESEM-EDX analysis of the produced fines shows precipitated salt, silica grain and kaolinite were migrated during scCO2 injection. It is suggesting that minerals were dissolved and precipitated, resulting in detachment of silica particles and formation of new secondary minerals, some of which plugged the pore spaces reducing the permeability. In addition, core saturated with CaCl2 brines are the only samples that showed permeability improvement after CO2 flooding experiment. Copyright 2020, Offshore Technology Conference